2018
DOI: 10.1186/s13104-018-3328-3
|View full text |Cite
|
Sign up to set email alerts
|

Global connectivity patterns of the notoriously invasive mussel, Mytilus galloprovincialis Lmk using archived CO1 sequence data

Abstract: ObjectiveThe invasive mussel, Mytilus galloprovincialis has established invasive populations across the globe and in some regions, have completely displaced native mussels through competitive exclusion. The objective of this study was to elucidate global connectivity patterns of M. galloprovincialis strictly using archived cytochrome c oxidase 1 sequence data obtained from public databases. Through exhaustive mining and the development of a systematic workflow, we compiled the most comprehensive global CO1 dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
(28 reference statements)
3
19
1
Order By: Relevance
“…Although the most congruent unilocus analysis (PTP: mean Ctax = 0.89) delimited in one species the blue mussels native to Argentina, Chile, Uruguay, Kerguelen Islands, New Zealand, Australia and Tasmania (see Fig 2 - groups d, e, f), the recovery of species from the General Mixed Yule Coalescent model (mean Ctax = 0.82) separated this clade into three species (d = Chile, part of Argentina, Uruguay and Kerguelen Islands; e = Australia; and f = New Zealand). Many previous studies have reported pronounced genetic differentiation between mussels from Australia/Tasmania and New Zealand (e.g., Gérard et al [ 18 ], Sanjuan et al [ 101 ], Pickett et al [ 102 ]). Therefore, the SDM results support the taxonomy described by Lamy [ 103 ] and Powell [ 104 ] who separated the Southwest Pacific Ocean mussels into two species: New Zealand animals were classified as Mytilus aoteanus Powell, 1958 (currently synonymous with M .…”
Section: Discussionmentioning
confidence: 99%
“…Although the most congruent unilocus analysis (PTP: mean Ctax = 0.89) delimited in one species the blue mussels native to Argentina, Chile, Uruguay, Kerguelen Islands, New Zealand, Australia and Tasmania (see Fig 2 - groups d, e, f), the recovery of species from the General Mixed Yule Coalescent model (mean Ctax = 0.82) separated this clade into three species (d = Chile, part of Argentina, Uruguay and Kerguelen Islands; e = Australia; and f = New Zealand). Many previous studies have reported pronounced genetic differentiation between mussels from Australia/Tasmania and New Zealand (e.g., Gérard et al [ 18 ], Sanjuan et al [ 101 ], Pickett et al [ 102 ]). Therefore, the SDM results support the taxonomy described by Lamy [ 103 ] and Powell [ 104 ] who separated the Southwest Pacific Ocean mussels into two species: New Zealand animals were classified as Mytilus aoteanus Powell, 1958 (currently synonymous with M .…”
Section: Discussionmentioning
confidence: 99%
“…The latter three are the most commercialized Mytilus species. Two other Chilean populations were sampled from locations where hybrid individuals have been found: Quillaipe (MCh-2) (n = 49) on the Gulf of Reloncaví 63 and the northern coast of the Gulf of Arauco (MG-2) (n = 50), where the Mediterranean mussel ( M. galloprovincialis ) has also been found 30,64 . Detailed sample data is included in Supplementary Information (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the shell is typically removed from processed foods, further hampering appearance-based identification 23 . Alternatively, mussels are characterized using genetic markers, with approaches relying on allozymes 2427 , sequencing of mitochondrial genes 2,2830 and PCR-based DNA markers, such as amplified fragment length polymorphisms (AFLP) 22 , random amplification of polymorphic DNA (RAPD) 31 , forensically informative nucleotide sequencing (FINS) 23 and fragment length polymorphisms (FLP). To enhance the specificity of FLP analysis, an enzymatic restriction step can be added to produce restriction fragment length polymorphism (RFLP) markers.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of the mitochondrial DNA (mtDNA) cytochrome c oxidase I (COI) gene to reveal ongoing genetic interactions between populations has been confirmed in extensive marine mollusks (Guo et al, 2015;Mao et al, 2011;Ni et al, 2012aNi et al, , 2012bWang et al, 2017), including M. galloprovincialis (Gerard et al, 2008;Han et al, 2017;Pickett and David, 2018). The present study compared three populations from intensive sampling along the China coast: farmed, naturalized adjacent to the farm, and isolated naturalized populations by amplifying COI sequences.…”
Section: Introductionmentioning
confidence: 99%